Legal Analysis of the Judge's Considerations in Supreme Court Decision Number 123 K/Pdt.Sus-PHI/2022 concerning Termination of Employment due to Company Efficiency - Affan, Ibnu; Rahmadani, Gema (Universitas Medan Area, 2025)
This study aims to analyze the judges' considerations in Supreme Court Decision Number 123 K/Pdt.Sus PHI/2022 regarding termination of employment (PHK) due to efficiency, particularly in the context of worker protection, legal certainty, and the application of labor norms. The study uses a normative juridical method with an approach of analyzing court decisions and legal literature. The results of the analysis show that the judge emphasized that termination of employment due to efficiency is legally valid if the employer can prove the existence of losses or potential losses to the company and has fulfilled the rights of workers, including severance pay, length of service awards, and compensation in accordance with PP 35/2021. The judges' considerations reflect the application of Law 13/2003, PP 35/2021, as well as the principles of worker protection, justice, and legal certainty, although the standard of proof for efficiency remains relatively flexible. This study concludes that the decision provides legal certainty for employers as well as adequate protection for workers, but requires consistent supervision and enforcement to maintain the principle of substantive justice. . While this ruling provides legal certainty for the disputing parties, academically, we need to examine the Ratio Decidendi, or the judge's underlying reasoning. The question is: How does the judge determine the threshold at which a company is deemed